2018
DOI: 10.1038/s41598-018-26281-z
|View full text |Cite
|
Sign up to set email alerts
|

Codon optimization and improved delivery/immunization regimen enhance the immune response against wild-type and drug-resistant HIV-1 reverse transcriptase, preserving its Th2-polarity

Abstract: DNA vaccines require a considerable enhancement of immunogenicity. Here, we optimized a prototype DNA vaccine against drug-resistant HIV-1 based on a weak Th2-immunogen, HIV-1 reverse transcriptase (RT). We designed expression-optimized genes encoding inactivated wild-type and drug-resistant RTs (RT-DNAs) and introduced them into mice by intradermal injections followed by electroporation. RT-DNAs were administered as single or double primes with or without cyclic-di-GMP, or as a prime followed by boost with RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 129 publications
0
32
0
Order By: Relevance
“…We used a method to assess the integral immune response against TERT which we named “antigen challenge” [ 47 ]. Specifically, we primed mice with TERT DNA or TERT-HA DNA, and then boosted with the same plasmids mixed with DNA encoding firefly luciferase (Luc DNA) ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We used a method to assess the integral immune response against TERT which we named “antigen challenge” [ 47 ]. Specifically, we primed mice with TERT DNA or TERT-HA DNA, and then boosted with the same plasmids mixed with DNA encoding firefly luciferase (Luc DNA) ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…We have earlier shown that immune response induced by DNA immunogen in prime eliminates cells coexpressing DNA immunogen and Luc after the boost with plasmid mixture. This results in a rapid loss of bioluminescence signal from the sites of booster injections in DNA-immunized mice compared to control mice [ 47 ]. Here, boosting of TERT or TERT-HA DNA-immunized mice with plasmids encoding TERT/TERT-HA and Luc resulted in a significant loss of bioluminescence signal in comparison to that in the control mice primed with pVAX1 and boosted with pVAX1 mixed with Luc DNA ( p < 0.05; Figure 2 B,C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations